MORPHOLOGICAL CHANGES IN THE INTESTINAL MUCOSA IN DUODENAL Peptic Ulcer (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
Peptic ulcer of the stomach and duodenum remains an urgent problem in clinical medicine. In my youth and middle age, it was traditionally associated with poverty and disability. In recent years, it has acquired particular importance in geriatric practice in connection with the peptic ulcer itself and its complications. All of the above dictates the need for the development of new clinical and organizational approaches to it for screening and prevention of sepsis in large growth groups.